A description of the potential growth and body composition of two commercial broiler strains. Issue 3 (3rd May 2020) - Vargas, L.; Sakomura, N. K.; Leme, B. B.; Antayhua, F.; Reis, M.; Gous, R.; Fisher, C.
ABSTRACT: 1. The potential growth of feathers and feather-free body and their chemical components was measured in two commercial broiler strains. 2. A total of 200 chicks of each sex x strain were fed adequate amounts of dietary protein using a four-phase feeding programme. Ten birds per genotype were sampled at 14, 28, 42, 56, 70, 84, 98 and 112 d of age. They were weighed before and after being dry-plucked to determine the weight of feathers, and the feather-free body was then minced and analysed for water, protein and lipid. 3. Body weights and chemical composition of males of the two strains were similar throughout the trial. Females of the two strains differed only in their body lipid contents, with mature Cobb females being higher than Ross (1371 vs . 1210 g). 4. Mature body weights of males and females from both strains averaged 8420 g and 6650 g; mature body protein weights averaged 1555 g and 1030 g; and mature body lipid contents averaged 908 and 1290 g, respectively. 5. Rates of maturing per day of body weights of males and females of both strains averaged 0.0385 and 0.0368; feather-free body protein was 0.0316 and 0.0348 and body lipid was 0.0503 and 0.0375, respectively. The rates for body lipid differed between Cobb and Ross females (0.0352 vs . 0.0397/d). Separate equations were required for males and females to describe the allometric relationship between lipid and protein in the feather-free body. 6. The rate of maturing of feathers in females was higher than in males (0.0526 vs . 0398/d) and the mature weight was lower (205 vs . 266 g), respectively. Mature body weights of broilers in this trial were considerably higher than those measured using the same protocol 24 years ago, whereas rates of maturing remained the same.